Conventional Primary Central Chondrosarcoma of the Pelvis: Prognostic Factors and Outcome of Surgical Treatment in 162 Patients. (21st February 2018) - Bus, Michaël P.A.; Campanacci, Domenico A.; Albergo, Jose I.; Leithner, Andreas; van de Sande, Michiel A.J.; Gaston, Czar Louie; Caff, Giuseppe; Mettelsiefen, Jan; Capanna, Rodolfo; Tunn, Per-Ulf; Jeys, Lee M.; Dijkstra, P.D. Sander
Abstract : Background: Studies focusing on the oncological outcome after treatment of conventional primary central chondrosarcoma of pelvic bone are lacking. We conducted this retrospective study at 5 referral centers to gain insight in the outcome of treatment for this tumor type and to identify risk factors for impaired oncological outcome. Methods: One hundred and sixty-two consecutive patients (118 male patients [73%]) who underwent resection of a conventional primary central chondrosarcoma of pelvic bone from 1985 to 2013 were evaluated. The median age was 51 years (range, 15 to 78 years). The median follow-up was 12.6 years (95% confidence interval [CI], 8.4 to 16.9 years). There were 30 grade-I lesions (19%), 93 grade-II lesions (57%), and 39 grade-III lesions (24%). Results: Sixty-two patients (38%) experienced local recurrence: 9 grade-I lesions (30%), 31 grade-II lesions (33%), and 22 grade-III lesions (56%). Forty-eight patients (30%) developed metastases. The risk of disease-related death was 3% for grade-I tumors (1 of 30; this patient had a grade-II recurrence and died of metastases), 33% (31 of 93) for grade-II tumors, and 54% (21 of 39) for grade-III tumors. Identified risk factors for impaired disease-specific survival were tumor grade (grade II: hazard ratio [HR], 20.18; p = 0.003; and grade III: HR, 58.94; p < 0.001), resection margins (marginal: HR, 3.21; p = 0.001; and intralesional: HR, 3.56; p < 0.001), and maximal tumor size (HR, 1.08 per cm; p = 0.026). Deep infection (19% [n = 31]) was the predominant complication. Conclusions: This study offers a standard for survival rates for conventional primary central chondrosarcoma of the pelvis. The survival for grade-I tumors was excellent. Wide resection margins were associated with a significant survival advantage for higher-grade tumors. Because of the inability to reliably distinguish low-grade and high-grade tumors preoperatively, we conclude that any central pelvic chondrosarcoma should be treated with aggressive primary resection with the aim of obtaining wide resection margins. There may be aggressive biologic features in some tumors for which a surgical procedure alone may not be adequate to improve outcomes. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.